OECD-407 Driven 28-day-repeated-dose non-clinical safety evaluation of Tinospora cordifolia (Giloy) stem aqueous extract in Sprague-Dawley rats under GLP compliance - Balkrishna, Acharya; Haldar, Swati; Varshney, Anurag (Frontiers in Pharmacology, 2023)
Tinospora cordifolia (Wild.) Hook.f. & Thomson (Giloy), has been widely used in the Ayurvedic system of medicine. However, some sporadic under-powered case studies have recently reported T. cordifolia associated toxicity. Thus, following OECD 407 guidelines, a 28-day-repeated-dose-14-day-recovery toxicological evaluation of the aqueous extract of T. cordifolia stem (TCWE) was conducted under good laboratory practice (GLP), in Sprague-Dawley (SD) rats. 100, 300, and 1000 mg/kg/day of TCWE was given orally to designated treatment groups of either sex. Two separate 14-day recovery satellite groups received either vehicle control or 1000 mg/kg/day of TCWE. In this study, TCWE was found safe up to a dose of 1000 mg/kg/day with no mortality or related toxicological manifestation in terms of clinical signs, ocular effects, hematology, urinalysis, clinical chemistry parameters, or macro- or microscopic changes in any organs. The satellite group did not show any adverse effect after 14-day recovery period. Thus, the No-Observed-Adverse-Effect-Level (NOAEL) of TCWE was determined to be 1000 mg/kg/day. In conclusion, this study established the non-clinical safety of the aqueous extract of T. cordifolia stem, which confirms the age-old safe medicinal use of this herb, and also paves the path for future clinical research on formulations containing Tinospora cordifolia.